Penampilan Tanaman Krisan Pot (Dendranthema grandiflora) pada Pemberian Pupuk Organik dan Anorganik - Firgiyanto, Refa; Rohman, Fadil; Sukri, M. Zayin; Kusparwanti, Tri Rini; Dinata, Gallyndra Fatkhu; Wardani, Windy Ayu (Agropross : National Conference Proceedings of Agriculture, 2023)
Potted chrysanthemum plants are known as one of popular room decoration elements because they have flowers of various shapes and colors as well as long-lasting freshness. Several aspects that many consumers value are the appearance of flowers and the balance between the plant stem and the pot. This aspect is influenced by the availability of nutrients from both organic and inorganic sources. Therefore, a research was conducted on the performance of potted chrysanthemum plants by application of organic fertilizers and inorganic fertilizers. This study aimed to determine the effect of organic and inorganic fertilizers on the growth and development of potted chrysanthemum plants. This research was conducted from June to October 2022 in Rembangan, Arjasa, Jember. This study used randomized block design (RBD). The experimental factors were the types and amount of fertilizers consisted of 12 levels, namely cow manure 15 g/polybag; guano fertilizer 15 g/polybag; compost 15 g/polybag; NPK (16-16-16): 150, 200, 250 ppm, NPK (15-15-15): 150, 200, 250 ppm and NPK Pelangi: 150, 200, 250 ppm. The observed variables included plant height, diameter of stem and crown and the number of branches and flowers. Data were analyzed using analysis of variance (ANOVA) with Duncan's Multiple Range Test (DMRT) with a level of 5%. Application of manure, guano and NPK (16-16-16) 200 ppm resulted in higher chrysanthemum plants compared to other treatments. Application of 150 ppm NPK Pelangi and 250 ppm NPK 15-15-15 showed the best results on the number of branches and the number of flowers.